Chemosensitivity of Anaplastic Thyroid Cancer Based on a Histoculture Drug Response Assay. (18th March 2015) - Uruno, Takashi; Masaki, Chie; Akaishi, Junko; Matsuzu, Kenichi; Suzuki, Akifumi; Ohkuwa, Keiko; Shibuya, Hiroshi; Kitagawa, Wataru; Nagahama, Mitsuji; Sugino, Kiminori; Ito, Koichi
Abstract : The chemosensitivity of anaplastic thyroid cancer (ATC) to some cytotoxic agents was investigated by the histoculture drug response assay (HDRA). Thirty specimens from 22 patients with ATC were obtained from surgically resected subjects. The drugs tested were paclitaxel (PTX), docetaxel (DOC), adriamycin (ADM), nedaplatin (254-S), cisplatin (CDDP), carboplatin (CBDCA), etoposide (VP-16), 5-fluorouracil (5-FU), mitomycin C (MMC), and cyclophosphamide (CPA). PTX was the most effective agent, and 25 of 29 cases (86.2%) had high inhibition rates (IRs; over 70%), while DOC, another taxane, had lower IRs (median, 32.6%). 254-S had the second highest IR (median 68.1%), higher than other platins, CDDP (median 47.3%) and CBDCA (median 27.4%). The IR of 50% dose PTX (20 μ g/mL, median 30.6%) was markedly decreased, while that of 50% dose 254-S (10 μ g/mL, median 63.3%) still retained its inhibition effect compared to 100% dose. Most recurrent samples had higher IRs than primary lesions, but the IRs of different drugs differed between primary and recurrent lesions, even with samples from the same patients. PTX has a higher IR to ATC tissues in the HDRA, which suggests that it may be a key drug for the treatment of patients with ATC.